Peripheral cellular immune alterations during excessive alcohol consumption - Karla Z. Medina-Avila; Abigail Hernandez-Barragan; Marisela Hernández-Santillan; Isabel Villagómez-López; Adrián Flores-Sanchez; Melanie Acosta-Gutiérrez; Viridiana Bautista-Nava; Isaac B Flores-Islas; Jesús A Dorantes-Álvarez; Moisés Martinez-Castillo; Fátima Higuera-de la Tijera; José L Pérez-Hernández; et al. (Annals of Hepatology)
Introduction and Objectives: The mechanisms that participate in the pathophysiology of chronic alcohol consumption and Alcoholic Liver Disease (ALD) include alterations of the innate and adaptive immune system, until now there is little information about the damage inducing mechanisms and their participation in the development of the disease. The objective was to determine the imbalance of peripheral cellular immunity according to the pattern of alcohol consumption. Materials and Patients: Cross-sectional study included 5 groups of subjects with different patterns of alcohol consumption using AUDIT and DSM-IV. G1: Control with OH consumption<10g/day (CT); G2: Risk (Ri) and G3: Abuse (A) with AUDIT>8; G4: Alcoholism, without clinical or biochemical stigmata of damage (OH); G5: Patients with alcoholic liver cirrhosis (CiOH). T cells, T-CD4+, T-CD8+, B cells, NK and NKT were determined in peripheral blood by flow cytometry. For statistical analysis we performed U-Mann Whitney, considering p<0.05 significant. Results: In the study, 589 subjects were included, average age 32±11, 30±11, 23±3, 31.5±13 and 47.5±7.7 years CT, Ri, A, OH y CiOH respectively (p<0.001). Alcohol consumption (g/day) was higher in OH 158(210,107), and CiOH 293(340,246) (p<0.001,both). Cellular determination of NK we found elevated (15.4 and 13.3vs11.1) and NKT (3.7 and 2.5vs1.7) in groups A, OH and CiOH (p<0.001), (p<0.001), (p<0.05) only in NK, during CiOH NKT decrease (1.4vs1.7)(p<0.001). In T cells we observed a decrease in OH (62.3vs66.5) and CiOH (56.8vs66.5) (p<0.001), the percentage of CD4+ cells decreased from the Ri group (35.7vs38.8)(p<0.01) until OH (35.1vs38.8)(p<0.01) while during CiOH they increase (41.8vs35.1)(p<0.05). CD8+ cells increase during OH (24.5vs21.1)(p<0.05) and decrease in CiOH (13.9vs21.1)(p<0.001) respectively. Conclusions: The immune abnormalities presented during risky consumption, abuse, dependence and cirrhosis due to alcohol are differential, the most significant changes are observed in the cytotoxic NK, NKT and CD8+ and regulatory CD4+ populations generating a cellular imbalance that could be related to development and progression of liver damage.